(untitled) (Communications in Computational Physics, 2020)
High speed particulate flow appears in many scientific and engineering problems. Current work focuses on the situation with volume fraction of particles between 0.001 and 0.5, in which both particle-fluid and particle-particle interactions are important. Based on the stratified multi-phase flow model (Chang & Liou, J. Comput. Phys. 225 (2007), 840-873) with Euler equations, by regarding one phase as solid, a numerical method is developed to conduct direct numerical simulations (DNS) to high speed particulate flows. It is then applied to simulate the problem with a planar shock wave impacting on a particle curtain, but focusing on the initial stage, in which the particles can be regarded as static. 2-D simulations are conducted by keeping the total volume fraction of particles and changing the number of particles. The convergence of shock wave locations and turbulent energy are observed. A 1-D volume-averaged model is also studied and compared with the DNS, which gives effective drag coefficients. A 3-D DNS is conducted to compare with the 2-D DNS and 1-D model, showing that more detailed 3-D DNS studies are needed. The convergent values obtained from current work can be applied to the study of very small particle cases and to the model development.